Association of breast cancer–related microRNA polymorphisms with idiopathic primary ovarian insufficiency. Issue 4 (April 2015) - Rah, HyungChul; Kim, Hyun Seok; Cha, Sun Hee; Kim, Young Ran; Lee, Woo Sik; Ko, Jung Jae; Kim, Nam Keun
Abstract Objective The aim of our study was to investigate whether breast cancer–related microRNA polymorphisms are associated with primary ovarian insufficiency (POI) risk. Methods Four breast cancer–related microRNA polymorphisms (miR-27aA > G [rs895819], miR-135bC > T [rs74141216], miR-423C > A [rs6505162], and miR-608G > C [rs4919510]) were genotyped in 136 women with idiopathic POI and 224 controls of Korean ethnicity using polymerase chain reaction–restriction fragment length polymorphism analysis. Differences in genotype frequencies between cases and controls were compared. Odds ratios and 95% CIs were determined as measures of the strength of association between genotype and POI. Results Two haplotypes (G-C-A-G and A-T-C-C) of miR-27a/miR-135b/miR-423/miR-608 were associated with increased POI risk. The haplotypes G-A-G of miR-27a/miR-423/miR-608 and A-T-C of miR-27a/miR-135b/miR-608 were associated with higher POI risk, whereas the G-T haplotype of miR-27a/miR-135b was associated with decreased POI risk. The association between POI risk and the G-A-G haplotype of miR-27a/miR-423/miR-608 remained significant after false discovery rate correction for multiple comparisons. The combined genotypes AA/CT/CC/CC, AG/CC/CA/GC, GG/CC/CC/CC, and GG/CC/CA/GG of miR-27a/miR-135b/miR-423/miR-608 were also associated with higher POI risk. Increased POI risk was observed in combined genotypes GG/CC/GG of miR-27a/miR-135b/miR-608; AA/CC/GC, AG/CA/GC, GG/CC/GG, GG/CC/CC, and GG/CA/GG of miR-27a/miR-423/miR-608; and GG/GG of miR-27a/miR-608; however, these associations were not significant after false discovery rate correction. None of the four microRNA polymorphisms alone was associated with POI risk. Conclusions Our data suggest that breast cancer–related microRNA polymorphisms, including miR-27aA > G, miR-423C > A, and miR-608G > C, are associated with increased POI risk via interactions between miR-27aG, miR-423A, and miR-608G variants. However, our results should be interpreted cautiously because of our small sample size and the low statistical power of our study design.